Innovative institutionalization using smart approaches - Nganwani Tia, Moses (Technical Centre for Agricultural and Rural Cooperation, 2019)
SavaNet-Ghana has innovatively institutionalised the experience capitalization approach using smart non-formal approaches which include a farmer-to-farmer capitalization platform, folk music, storytelling and drama. This article highlights the steps taken, and some of the obstacles seen